2011
DOI: 10.1007/s10530-010-9933-2
|View full text |Cite
|
Sign up to set email alerts
|

Competitive interactions between co-occurring invaders: identifying asymmetries between two invasive crayfish species

Abstract: Ecosystems today increasingly suffer invasions by multiple invasive species. Complex interactions between invasive species can have different fitness implications for each invader, which can in turn determine the future progression of their invasions and result in differential impacts on native species and ecosystems. To this end, through pairwise and group scale experiments, we examined possible interaction outcomes, competition effects and their potential fitness implications for two widespread invasive spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 70 publications
(88 reference statements)
1
43
0
Order By: Relevance
“…As allometric growth of certain body parameters (claws in males, abdomen in females) is a determinant of sexual dimorphism and reflects the onset of sexual maturity (Harioglu and Holdich, 2001;Streissl and Ho¨dl, 2002), both sexes were divided into two size classes: size class 1, animals < 9 cm TL (potentially immature individuals); and size class 2, animals > 9 cm TL (mature individuals). Such classification was based upon the large size of the smallest caught mature female recorded during year cycle research at M1 (85 mm TL; Hudina et al, 2011) which was close to the upper range of signal crayfish size at maturity recorded in the literature (6-9 cm TL; Westman et al, 1999;SoutyGrosset et al, 2006). Finally, in order to take into account the potential allometric growth in adult (i.e., mature) males and females, measured claw and abdomen parameters were compared between the sites as relative proportion of each respective parameter to TL.…”
Section: Inter-population Comparisonsmentioning
confidence: 55%
See 1 more Smart Citation
“…As allometric growth of certain body parameters (claws in males, abdomen in females) is a determinant of sexual dimorphism and reflects the onset of sexual maturity (Harioglu and Holdich, 2001;Streissl and Ho¨dl, 2002), both sexes were divided into two size classes: size class 1, animals < 9 cm TL (potentially immature individuals); and size class 2, animals > 9 cm TL (mature individuals). Such classification was based upon the large size of the smallest caught mature female recorded during year cycle research at M1 (85 mm TL; Hudina et al, 2011) which was close to the upper range of signal crayfish size at maturity recorded in the literature (6-9 cm TL; Westman et al, 1999;SoutyGrosset et al, 2006). Finally, in order to take into account the potential allometric growth in adult (i.e., mature) males and females, measured claw and abdomen parameters were compared between the sites as relative proportion of each respective parameter to TL.…”
Section: Inter-population Comparisonsmentioning
confidence: 55%
“…1), where the highest dispersal rates of signal crayfish in Europe have been recorded by previous studies (Hudina et al, 2009). Signal crayfish populations at the most upstream sites of this section have been established for over 5 years and have reached relatively high population densities and balanced sex structure (Hudina et al, 2011). Therefore, the most upstream examined site is considered to represent a source population in the examined river section.…”
Section: Study System and Sampled Populationmentioning
confidence: 90%
“…Species replacements can also be affected by how standing behavioral variation within the invading population is spatially structured [15,[50][51][52]. For example, male western bluebirds at the invasion front are more aggressive than those in the resident population [15].…”
Section: Behavioral Interference In Competition Experimentsmentioning
confidence: 99%
“…Aggressive interference in conjunction with habitat changes appears to account for the cyclical replacement of mountain bluebirds (Sialia currucoides) by western bluebirds (Sialia mexicana) in the northwestern USA [15]. Likewise, aggressive and reproductive interference combined with climate change appear to be driving the replacement of pied flycatchers (Ficedula hypoleuca) by collared flycatchers (Ficedula albicollis) on the Swedish Island of Öland [16,48].Species replacements can also be affected by how standing behavioral variation within the invading population is spatially structured [15,[50][51][52]. For example, male western bluebirds at the invasion front are more aggressive than those in the resident population [15].…”
mentioning
confidence: 99%
“…The increase in proportion of overall injuries observed in July and August might be associated with molting. Finally, as claws represent a valuable and frequently damaged tool in aggressive interactions between crayfish (Schroeder and Huber, 2001) and proportion of claw injuries is frequently used as an indirect measure of competition intensity (Söderbäck, 1991;Hudina et al, 2011), the observed increase in the proportion of claw injuries in October is assumed to be the result of intensified competition during mating season. In analyses of signal crayfish movement patterns, the recorded values of cumulative distance moved by crayfish were in line with data obtained from other studies of signal crayfish spatial behavior (Bubb et al, 2002(Bubb et al, , 2004(Bubb et al, , 2006a(Bubb et al, , 2006bLight, 2003), while mean daily movement was substantially higher than in other analyzed populations (Bubb et al, 2004(Bubb et al, , 2006a.…”
Section: Discussionmentioning
confidence: 99%